Macroeconomic indicators and capital market performance: Are the links sustainable? - Felicia O. Olokoyo (Taylor & Francis Group, 2020)
This paper examines the long-run impact of macroeconomic indicators such as interest rate, foreign capital flows, exchange rate, GDP growth, inflation and trade on stock market performance (market capitalization) in Nigeria. Using data drawn from the World Development Indicators (WDI, 2018) and the Central Bank of Nigeria (CBN) Statistical Bulletin 2018, the study employed the VECM analysis. The results found suggest that 1) macroeconomic variables and stock market performance are cointegrated and thus linked in the long run; 2) interest rate, inflation and trade bear a negative relationship with stock market performance; and 3) exchange rate, GDP growth rate and foreign capital flows are positively related to stock market performance. Our results show that when there is a deviation from the long-run relation between stock market performance and mafcroeconomic fundamentals, it is primarily the stock market, interest rate and foreign capital flows that adjust to ensure that the long-run link is restored, whereas exchange rate, GDP growth, inflation and trade are weakly exogenous. We estimate that any disequilibrium emanating from interest rate is more than fully corrected in one year, in the oscillating convergence sense, while 29% and 5% of the disequilibrium from stock market and foreign capital flows are corrected in one year. A policy recommendation that emerges from the study is the need to strengthen policies aimed at improving the country’s macroeconomic environment. Specifically, this will involve policies aimed at lowering interest rate, increasing foreign capital flows and improving the country’s terms of trade.